2023
DOI: 10.1002/anie.202301074
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Platinum(IV) Prodrug Hemoglobin Nanoparticles with Deeply Penetrating Ultrasound Radiation for Tumor‐Targeted Therapeutically Enhanced Anticancer Therapy

Abstract: The development of Pt IV prodrugs that are reduced into the therapeutically active Pt II species within the tumor microenvironment has received much research interest. In order to provide spatial and temporal control over the treatment, there is a high demand for the development of compounds that could be selectively activated upon irradiation. Despite recent progress, the majority of Pt IV complexes are excited with ultraviolet or blue light, limiting the use of such compounds to superficial application. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Furthermore, the adoption of alternative activation strategies, such as photoactivation or sonosensitization, will be a practical approach to accelerate the reduction process of alkoxido platinum(IV) complexes and enhance their anticancer efficacy within tumor tissues. [60][61][62][63][64][65][66]…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the adoption of alternative activation strategies, such as photoactivation or sonosensitization, will be a practical approach to accelerate the reduction process of alkoxido platinum(IV) complexes and enhance their anticancer efficacy within tumor tissues. [60][61][62][63][64][65][66]…”
Section: Resultsmentioning
confidence: 99%
“…A variety of nanomaterials are typically used to deliver bioactive molecules and living bio-organisms to form nanomedicines through physical encapsulation, electrostatic interactions, and chemical conjugation. In addition, intratumor endogenous stimuli (pH, enzyme, redox , ), as well as exogenous stimuli (light, electricity, , sound, magnetism, heat ), can be applied to trigger the breakdown of sophisticated chemical bonds and/or physical structures of drug carriers to release the active ingredients. Therefore, it is generally assumed that once the nanomedicines enter cancer cells, the active anticancer agents could be released to exert the anticancer effect.…”
Section: Fundamental Question Of Nanomedicinesmentioning
confidence: 99%
“…Within the past two decades, increasing attention has been focused on pincer platinum complexes due to their attractive biological and photophysical properties (i.e., high water solubility, high biocompatibility, strong luminescence, and large Stokes shift). Recent studies in the materials science field have indicated that pincer metal complexes could self-assemble into nanomaterials through π–π stacking and hydrophobic interactions. The self-assembly properties of these metal complexes are dependent on various factors including but not limited to solvent polarity, concentration, type of anion, temperature, or pH. …”
Section: Introductionmentioning
confidence: 99%